2020
DOI: 10.1016/j.nicl.2020.102419
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of the structural connectome in primary open angle Glaucoma

Abstract: Highlights Primary Open Angle Glaucoma is one of the major causes of blindness worldwide. Structural connectivity and graph theory allow to analyse brain network changes. Disruption index is able to estimate the reorganization of nodal network topology. The global network of Primary open angle Glaucoma patients is highly reorganized. Primary open angle glaucoma could be considered a neurodegenerative disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 83 publications
2
13
0
Order By: Relevance
“…Thus, we speculated that the PACG might lead to the reorganization of auditory and cognitive function. Similar results that no disruption of measures were also observed in a previous study regarding glaucoma patients ( 39 41 ), hinting that the efficiency of communication in the brain network was conserved and the brain was homogeneously well reorganized.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, we speculated that the PACG might lead to the reorganization of auditory and cognitive function. Similar results that no disruption of measures were also observed in a previous study regarding glaucoma patients ( 39 41 ), hinting that the efficiency of communication in the brain network was conserved and the brain was homogeneously well reorganized.…”
Section: Discussionsupporting
confidence: 88%
“…NTG changes the information processing in the brain by reorganizing the information flows between visual cortices and non-visual brain areas, and these alterations are consistent with microstructural injury of visual cortices [ 69 ]. Li reported decreased information outflows in NTG patients from the left BA17 to bilateral cuneus and increased effective connectivity, reflecting integration within a distributed system, from BA19 and BA18 to cuneus (BA17) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study showed that, while the diffuse structural and functional abnormalities of the entire brain during glaucoma are partially due to nerve damage and degeneration caused by elevated intraocular pressure, they are also partially independent of elevated intraocular pressure and subsequent retinal degeneration (Giorgio et al, 2018 ). Recent imaging evidence shows that in the imaging examination of glaucoma patients, the effective connectivity between the visual cortex and the entire brain is significantly reduced (Li et al, 2020 ), and the decrease in visual acuity in POAG patients is driven by a combination of local (i.e., in the eyes) and broader (i.e., brain) effects (Di Cio et al, 2020 ). Studies of both animal models and human glaucoma patients have shown that there is damage to the central nervous system during glaucoma.…”
Section: Transneuronal Degeneration In Glaucoma Brainmentioning
confidence: 99%